Response Bias in Research on Religion, Spirituality and Mental Health: A Critical Review of the Literature and Methodological Recommendations - Maraldi, Everton de Oliveira (Journal of religion and health, 2020)
Although a significant body of research supports the psychological benefits of religion and spirituality, more investigations are needed to understand the mechanisms by which they impact mental health. While some studies suggest a causal direct influence, the findings may still be subject to unmeasured factors and confounders. Despite compelling empirical support for the dangers of response bias, this has been a widely neglected topic in mental health research. The aim of this essay is to critically examine the literature addressing the role of response bias in the relationship between religion, spirituality and mental health. A survey of the diverse types of bias in this research area is presented, and methodological and theoretical issues are outlined. The validity and generalizability of the evidence are discussed, as well as the implications for mental health practice. A list of methodological remedies to reduce bias is suggested. The article is then concluded with a summary of the studies reviewed and directions for future research.